Late Quaternary vegetation of Chukotka (Northeast Russia), implications for Glacial and Holocene environments of Beringia. (1st January 2015) - Anderson, Patricia M.; Lozhkin, Anatoly V.
Abstract: Two lake records from the Kankaren region of southern Chukotka, when combined with other palynological and macrofossil data, document spatial and temporal variations in the regional vegetation history since ∼21, 000  14 C/25, 400 cal yr BP. Full-glacial environments were severely cold and arid in central and northern Chukotka, whereas southern sites experienced conditions that were relatively moist, although still drier than present. Southern Chukotka may represent a western extension of environments of the land bridge proper, including a possible "moisture" barrier to intercontinental migration. Shrub Betula tundra established earliest in southern Chukotka (∼15, 800–14, 000  14 C/19, 000–16, 700 cal yr BP; ∼13, 000  14 C/15, 300 cal yr BP central and north), Pinus pumila earliest in the north (∼9600  14 C/11, 100 cal yr BP; ∼7600  14 C/8400 cal yr BP south), and shrub Alnus earliest in both the south and north (∼12, 000–11, 000  14 C/13, 800–12, 900 cal yr BP). These patterns support the presence of cryptic refugia for Betula and Alnus in Chukotka during the full glaciation. In contrast, P. pumila probably migrated into Chukotka from populations located in the northern coastal lowlands and from mountainous regions of southwestern Beringia. Evidence for a thermal optimum (∼11, 000–8000  14 C/12, 900–9000 cal yr BP) is strong in northern Chukotka but is absent in central and southern areas. Highlights: Relatively mesic settings characterized south Chukotka during the full glaciation. Betula and Alnus c ryptic refugia existed in Chukotka during the full glaciation. North lowland source of some Holocene populations of Pinus pumila in Chukotka. Evidence for a PGTM is strong in north but weak in central and south Chukotka.